(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The thyroid gland is a critical organ of the endocrine system that regulates metabolism, growth, and sexual maturation. During puberty, endocrine regulation undergoes significant restructuring, and even moderate fluctuations in thyroid function can affect metabolism and body weight. To investigate the functional state of the thyroid gland in overweight adolescent girls living in iodine-deficient conditions. A cross-sectional study was conducted involving 150 girls aged 12-17 years. Anthropometric measurements, thyroid-stimulating hormone (TSH), free thyroxine (fT4), free triiodothyronine (fT3), and anti-thyroid peroxidase antibodies (anti-TPO) were assessed. Sexual maturation was evaluated using the Tanner scale. Girls with excess weight demonstrated significantly higher levels of TSH and fT3. A positive correlation was found between body mass index (BMI) and TSH (r equals 0.52, p less than 0.001).